Effects of Polypropylene Fibers and Flyash in Self Compacting Concrete - Deepak G Appaji, Dr. Chethan.K (International Journal of Advanced Science and Technology, 2020)
Self-Compacting concrete is being adopted by various application. Addition of fibers to SCC has shown to improve strength and durability in concrete. The current study presents an investigation on compressive strength in polypropylene fiber reinforced SCC. Six mixes of concrete with varying percentage of fibers (1% and 2%) are considered. Strength Mix-S (100% Cement) shows more strength then Mix-S1(100% cement with 1%PPF) & Mix-S2(100% cement with 2%PPF) similarly Mix-SF (70% cement + 30% Flyash) shows more strength the Mix-SF1(70% cement + 30% Flyash with 1%PPF) and Mix-SF2(70% cement + 30% Flyash with 2%PPF).